CHIP modulates APP‐induced autophagy‐dependent pathological symptoms in Drosophila. Issue 2 (28th November 2019) - Zhuang, Luming; Peng, Fei; Huang, Yuanyuan; Li, Wenzhe; Huang, Jiuhong; Chu, Yunqiang; Ren, Pu; Sun, Ying; Zhang, Yan; Xue, Elleen; Guo, Xiaowei; Shen, Xiafeng; et al.
Abstract: Dysregulation of autophagy is associated with the neurodegenerative processes in Alzheimer's disease (AD), yet it remains controversial whether autophagy is a cause or consequence of AD. We have previously expressed the full‐length human APP in Drosophila and established a fly AD model that exhibits multiple AD‐like symptoms. Here we report that depletion of CHIP effectively palliated APP‐induced pathological symptoms, including morphological, behavioral, and cognitive defects. Mechanistically, CHIP is required for APP‐induced autophagy dysfunction, which promotes Aβ production via increased expression of BACE and Psn . Our findings suggest that aberrant autophagy is not only a consequence of abnormal APP activity, but also contributes to dysregulated APP metabolism and subsequent AD pathogenesis. Abstract : CHIP modulates APP‐induced Aβ production and pathological symptoms. CHIP promotes APP‐induced aberrant autophagy. Autophagy contributes to APP‐induced pathological symptoms. Autophagy regulates Aβ production and amyloid deposits.